Discovery of Genomic Characteristics and Selection Signatures in Southern Chinese Local Cattle - Liu, Yuqiang; Xu, Lingyang; Yang, Liu; Zhao, Guoyao; Li, Junya; Liu, Dewu; Li, Yaokun (Frontiers in Genetics, 2020)
Abstract Chinese local cattle are mainly originated from two subspecies, with cattle in the north and northeast China are primarily of Bos t. taurus ancestry and cattle in southern China are predominantly of Bos t. indicus. Cattle from southern China are characterized with specific phenotype and adaptive for local environment. The purpose of this study is to understand the level of genetic diversity and the extent of admixture and selection signature of local cattle breed in southern China. Results We performed genetic diversity analysis using a total of 568,129 high quality SNPs in eight breeds from Southern China. Among them, we found the highest level of heterozygosity in Zhaotong cattle from Yunnan, whereas the lowest level of heterozygosity was detected Hainan and Nandan cattle from Guangzhou and Guangxi. The Neighbor-joining phylogenetic tree clearly separated Lufeng cattle from other breeds, while Leiqiong and Hainan cattle are mixed together. Based on a LD pruned SNPs, the admixture analysis revealed two clusters corresponding to taurine and zebu cattle lineages, and these eight local breeds from southern China showed different degrees of admixture between taurine and zebu cattle. When K = 3 and 9, we found the clustering pattern implied the remarkable division of between Leiqiong cattle, Lufeng and Hainan cattle. Moreover, we observed Leiqiong and Hainan were cluster together, which suggested close genetic relationship among them.We identified a total of 568,129 SNPs as outlier for selection across genome using Bayescan method. Moreover, we observed several candidate genes under selection which are related to growth, meat quality, immunity and adaption for local environments in southern China. Conclusion Our results provide significant information about genetic differentiation of cattle breeds from Southern China and the possible cause of differences in breed-specific features. Further analysis of selection signature suggested a list of candidate SNPs and candidate genes associated with important traits, which would provide valuable insight into elucidating genetic basis of traits under selection in local cattle.